Progress and Challenges in Microalgal Biodiesel Production - Mallick, Nirupama; Bagchi, Sourav K.; Koley, Shankha; Singh, Akhilesh K. (Frontiers in Microbiology, 2016)
The last decade has witnessed a tremendous impetus on biofuel research due to the irreversible diminution of fossil fuel reserves for enormous demands of transportation vis-a-vis escalating emissions of green house gasses (GHGs) into the atmosphere. With an imperative need of CO2 reduction and considering the declining status of crude oil, governments in various countries have not only diverted substantial funds for biofuel projects but also have introduced incentives to vendors that produce biofuels. Currently, biodiesel production from microalgal biomass has drawn an immense importance with the potential to exclude high-quality agricultural land use and food safe-keeping issues. Moreover, microalgae can grow in seawater or wastewater and microalgal oil can exceed 50-60% (dry cell weight) as compared with some best agricultural oil crops of only 5-10% oil content. Globally, microalgae are the highest biomass producers and neutral lipid accumulators contending any other terrestrial oil crops. However, there remain many hurdles in each and every step, starting from strain selection and lipid accumulation/ yield, algae mass cultivation followed by the downstream processes such as harvesting, drying, oil extraction and biodiesel conversion (transesterification), and overall, the cost of production. Isolation and screening of oleaginous microalgae is one pivotal important upstream factor which should be addressed according to the need of freshwater or marine algae with a consideration that wild-type indigenous isolate can be the best suited for the laboratory to large scale exploitation. Nowadays, a large number of literature on microalgal biodiesel production are available, but none of those illustrate a detailed step-wise description with the pros and cons of the upstream and downstream processes of biodiesel production from microalgae. Specifically, harvesting and drying constitute more than 50% of the total production costs; however, there are quite a less number of detailed study reports available. In this review, a pragmatic and critical analysis was tried to put forward with the on-going researches on isolation and screening of oleaginous microalgae, microalgal large scale cultivation, biomass harvesting, drying, lipid extraction and finally biodiesel production.